Assessment of Major Neurocognitive Disorders in Primary Health Care: Predictors of Individual Risk Factors - Sousa, Susana; Teixeira, Laetitia; Paúl, Constança (Frontiers in Psychology, 2020)
Major Neurocognitive Disorders describe the symptoms of a large group of diseases causing a progressive decline in individual's functioning. It is an umbrella term describing a decline in memory, intellectual ability, reasoning and social skills, as well as changes in normal emotional reactions. The general practitioner is instrumental in the early diagnosis of Major Neurocognitive Disorder. Individual risk factors act as contributing variables affecting the probability of someone developing a Major Neurocognitive Disorder and may be considered predictive factors. This study aimed (i) to show the utility of using the Global Deterioration Scale in primary health care settings as a measure to assess the stage of cognitive function for individuals identified with Major Neurocognitive Disorders and(ii) to identify predictors of severe Major Neurocognitive Disorders. Potential predictors of Major Neurocognitive Disorders considered in this study were: sex, age, years of education, social isolation, hearing impairment, cardiovascular disease, hypertension, diabetes, smoking habits, alcohol consumption, physical activity, hand strength and nutritional status. The sample comprised 250 adults, 30.4% were classified as having probable Major Neurocognitive Disorder. The variables significantly associated with probable Major Neurocognitive Disorder were age, years of education, hearing impairment, cardiovascular disease, hand strength, nutritional status and physical activity. In the multivariable model, only age, education, physical activity and hand strength remained significant predictors of probable Major Neurocognitive Disorder. The Global Deterioration Scale seems to be a usefull instrument in primary healthcare settings, as it guides the general practitioner in observing the patients’ cognitive functioning. Advanced age, lower education, lower hand strength and absence of physical activities should be taken into account as they increase the chance of severe Major Neurocognitive Disorders. Primary health care providers, including general practitioners are very important in the diagnosis and follow up of Major Neurocognitive Disorder. The general practitioner is in most cases the patients' first and for many patients the only contact, thus having a critical role in evaluating with caution what is part of normal or pathological aging, and the individual factors that can increase the likelihood of developing Major Neurocognitive Disorder to further support patients in the course of the disease.